A truncating mutation in CEP55 is the likely cause of MARCH, a novel syndrome affecting neuronal mitosis. Issue 7 (6th March 2017) - Frosk, Patrick; Arts, Heleen H; Philippe, Julien; Gunn, Carter S; Brown, Emma L; Chodirker, Bernard; Simard, Louise; Majewski, Jacek; Fahiminiya, Somayyeh; Russell, Chad; Liu, Yangfan P; ,; et al.
Abstract : Background: Hydranencephaly is a congenital anomaly leading to replacement of the cerebral hemispheres with a fluid-filled cyst. The goals of this work are to describe a novel autosomal-recessive syndrome that includes hydranencephaly (multinucleated neurons, anhydramnios, renal dysplasia, cerebellar hypoplasia and hydranencephaly (MARCH)); to identify its genetic cause(s) and to provide functional insight into pathomechanism. Methods: We used homozygosity mapping and exome sequencing to identify recessive mutations in a single family with three affected fetuses. Immunohistochemistry, RT-PCR and imaging in cell lines, and zebrafish models, were used to explore the function of the gene and the effect of the mutation. Results: We identified a homozygous nonsense mutation in CEP55 segregating with MARCH. Testing the effect of this allele on patient-derived cells indicated both a reduction of the overall CEP55 message and the production of a message that likely gives rise to a truncated protein. Suppression or ablation of cep55l in zebrafish embryos recapitulated key features of MARCH, most notably renal dysplasia, cerebellar hypoplasia and craniofacial abnormalities. These phenotypes could be rescued by full-length but not truncated human CEP55 message. Finally, we expressed the truncated form of CEP55 in human cells, where we observed a failure of truncated protein to localise to the midbody, leading to abscission failure and multinucleated daughter cells. Conclusions: CEP55 loss of function mutations likely underlie MARCH, a novel multiple congenital anomaly syndrome. This association expands the involvement of centrosomal proteins in human genetic disorders by highlighting a role in midbody function.